Comprehensive analysis of prognosis of cuproptosis-related oxidative stress genes in multiple myeloma - Li, Tingting; Yao, Lan; Hua, Yin; Wu, Qiuling (Frontiers in Genetics, 2023)
Multiple myeloma (MM) is a highly heterogeneous hematologic malignancy. The patients' survival outcomes vary widely. Establishing a more accurate prognostic model is necessary to improve prognostic precision and guide clinical therapy. Our study combined cuproptosis, a novel identified form of programmed cell death, and oxidative stress to evaluate the prognosis of MM patients. We developed an eight-gene model to assess the prognostic outcome of MM patients by univariate Cox analysis, Least absolute shrinkage and selection operator (LASSO) regression and multivariate Cox regression analyses. Other independent databases were used to validate the model. The results showed that the overall survival of patients in the high-risk group was significantly shorter compared with that of those in the low-risk group. In conclusion, the eight-gene risk model can provide valid predictions for prognosis and guide personalized clinical treatment.